2021
DOI: 10.1016/j.ejim.2021.05.028
|View full text |Cite
|
Sign up to set email alerts
|

kinetics of anti-SARS-CoV-2 antibodies over time. Results of 10 month follow up in over 300 seropositive Health Care Workers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 31 publications
5
29
0
Order By: Relevance
“…Our study confirms that most individuals would keep their antibodies for 10 months or longer. Our results agree as well to others reporting a high percentage of individuals (above 75%) keeping antibodies positive for at least 9 months even when a titer decline is patent [14]. That would mean at least resolution of symptoms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study confirms that most individuals would keep their antibodies for 10 months or longer. Our results agree as well to others reporting a high percentage of individuals (above 75%) keeping antibodies positive for at least 9 months even when a titer decline is patent [14]. That would mean at least resolution of symptoms.…”
Section: Discussionsupporting
confidence: 93%
“…Specific anti SARS-CoV-2 immunoglobulin loss would be a rare event slightly more frequent in women and a decay would be more frequent in younger donors. Mature age would determine longer antibody half-life [14]. Ageing is one of the most important determinants in COVID-19 severity [16,17] and it would have a role as well in humoral response keeping but larger cohorts and replication analyses should be performed to determine whether a an age-titer correlation exists because of the small rate of waning cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that serum IgG antibody levels, as well as neutralizing antibody titers decline over time in COVID-19 recovering patients, as was established in well-controlled longitudinal observational studies [ 12 , 13 ]. Therefore, it is especially important to understand for how long the virus-specific T cells are maintained, as they can rapidly respond to re-infection and protect individuals by activating robust antibody production and or via the cytotoxicity mechanism leading to fast elimination of the pathogen from the infected organism [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to symptomatic HCW, those who were asymptomatic or had mild symptoms were at almost seven times higher risk of being seronegative, corroborating previous reports ( 8 11 ). It has been reported that severity of COVID-19 affects the initial magnitude but not persistence of antibodies ( 3 ), Although a recent study demonstrated that antibodies decline over time and their half-life is positively associated with the intensity of the initial response ( 12 ). We do not present data implying a correlation between initial antibody response and antibody persistence, as we did not measure antibody titers initially or at the following time points.…”
Section: Discussionmentioning
confidence: 99%